State-business relations and the politics of state aid in the European Union: a multi-method approach to explaining aid allocations among member states - Schito, Marco (Trinity College Dublin. School of Social Sciences & Philosophy. Discipline of Political Science, 2021)
This thesis investigates state aid allocations in the European Union (EU) member states to answer two key research questions about the political management of a market economy. Today, government officials cannot be indifferent to business performance. When direct management of the economy is not feasible, the government's role is to induce business to perform well. One way to do so is through the allocation of targeted subsidies to firms. However, not all countries support domestic producers to the same extent. Thus, the first research question it seeks to answer is: why do some national governments grant more state aid than others? In Chapter 2, I argue that political actors' incentives depend on the broad configuration of domestic and international political-economic institutions and structures, which interact to shape economic outcomes. My argument hinges on the two key words of responsiveness and accountability. With the former, I want to highlight the use of subsidies as a governmental instrument for the pursuit of a policy goal such as those mentioned above, and the degree to which these goals reflect the voters' preferences. By the latter term, I mean the possibility for the voters to identify who is responsible for policy decisions and to oust officeholders whose performance they find unsatisfactory. The need for politicians to secure re-election incentivises strategic policy-makers to use policies such as subsidies that can bring large and clear net benefits to voters, thus improving their electoral fortunes. The results, expounded in Chapter 3, show that government responsiveness to societal demands is negatively affected by power-sharing arrangements, in particular the presence of coalition partners, and international commitments, such as the regulation of state aid. These results, however, become non-significant when, in Chapter 4, the analysis closes in on one key economic sector of several EU member states, the automotive industry. On the contrary, the accountability side of the story seems to be consistent across the two analyses. This leads to a further line of inquiry: how can we understand state-business relations in state aid politics in terms of responsiveness and accountability? This second question builds on the first one and expands the scope of analysis by looking not merely at the political determinants of aid allocations, but rather at the very dynamics at the heart of state aid politics, showing how state and business interact in this domain. To answer this question, I operate a dual shift of analysis, which was partially initiated with the within-sector investigation in Chapter 4. First, I shift the level of analysis from the macro-level to the meso-level by introducing the policy network approach in Chapter 5. This theoretical framework of interest intermediation based on resource exchange not only complements the macro-level account of state aid politics, but it is also better able to capture the relationship between firms and state agencies by providing a more fine-grained analysis thereof. Secondly, I also shift the methodological approach from regression-based to a mixture of comparative-historical analysis, which investigates state-business relations, and text and content analyses of parliamentary questions, which instead explore parliamentarians' incentives to support domestic producers for electoral goals. To this aim, three member states were chosen as case studies to maximise variation across the independent variables when matched: Italy, Britain and France, which are analysed in Chapters 6, 7 and 8, respectively. In the first part of each chapter, I offer a historical analysis of state-business relations concerning subsidy allocations to the automotive industry. Then, I also provide an explanation, based on the policy network approach, as to why the particular configuration of state-business relations at one time led to specific outcomes of industrial policy and aid disbursement decisions in the industry. The second part of each chapter first presents the electoral system (or systems) of each country, along with other features that are relevant to electoral politics, such as candidate selection. After that, I investigate how parliamentarians approach questions by looking at the most frequently used words, at who asked the question, and whether or not the question could be seen as the parliamentarian engaging in constituency service. Two findings of these case studies stand out. First, regardless of the political system, there is a persistent use of subsidies as a reactive policy tool, employed more as a means to maintain the status quo in the sector rather than innovate and set up an industrial agenda. This, instead, is better explained by the nature of the sectoral policy network in each country. Secondly, parliamentarians only partly follow electoral incentives when tabling questions. Part of their behaviour seems to be instead influenced by the typology of policy network within the sector, although the direction of the effect and the causal mechanism remain unclear. The case studies prove the usefulness of this double shift of analysis, which helped in at least two respects. First, it helped bridge the macro-level findings with the sectoral-level ones. Without the sectoral regression analysis, the rest of the findings would have been contradictory, leading to wrong inferences. Secondly, it showed that, unlike what the regression findings may suggest, there is no automatic translation of how electoral institutions influence legislative behaviour to lobby for subsidies. The wider implications of this study travel across several literatures. The theoretical framework offered in Chapter 2 can be applied not only to state aid allocations, but to a variety of other policies of state intervention in business politics, such as foreign direct investment, mergers & acquisitions, privatisations, tariffs, and product market regulation. Further, other sectors beyond the automotive industry can be analysed in the same way to explore in particular the political clout that multinational corporations today have over national governments. Thirdly, by uncovering some of the shortcomings of the policy network approach that come to the fore particularly when considering the globalised and Europeanised economic environment of today, this work can contribute to its future developments. Finally, this work can also set an agenda to better investigate the interlinking of policy network and electoral politics.
APPROVED
Keywords: state aid; distributive politics; competition policy; European politics; electoral politics; automotive industry